A Systematic Literature Review on Second Language Acquisition through the Lens of Complex Dynamic Systems Theory: Mapping Research Contexts, Methodological Trends, and Thematic Findings - Puspito Rizky Wahani; Widhiyanto (Journal of English Language Learning, 2026)
Abstract: Recent advances in second language acquisition research highlight contextual and interconnected developmental processes, but qualitative and process-oriented studies grounded in Complex Dynamic Systems Theory (CDST) remain limited and insufficiently synthesized. This study reviews qualitative CDST-informed SLA research published between 2015 and 2025 to map research context, methodological trends, and major thematic findings. A qualitative systematic literature review was conducted across various databases and utilized reference management software, following the PRISMA guidelines framework for Systematic Reviews and Meta-Analyses. Data were thoroughly analysed employing the inductive thematic synthesis and descriptive mapping. The findings indicate that CDST-informed research consistently conceptualizes L2 development as a nonlinear, variable, and context-sensitive process, with implications for process-oriented research and pedagogy.